Israel and the Creation of a Palestinian State : A European Perspective - J. H. H. Weiler (Routledge, 2024)
To many outside observers of the Israeli-Palestinian conflict, there would appear to be one eminently sensible solution: in exchange for recognition and adequate security guarantees, Israel should return the West Bank and the Gaza strip, subject to minor boundary modifications, to the Palestinians (led by a moderate PLO). The Palestinians would then exercise their right to self-determination and establish an independent state with or without a link to Jordan. And yet, this solution has found favor neither with successive Israeli governments nor with the PLO.First published in 1985, Israel and the Creation of a Palestinian State (now with a new preface by the author) analyses the reasons for the rejection of this solution by the protagonists. It then sets up a vision of a possible solution which, by taking account of the subjective fears and aspirations of the parties, may be regarded as more feasible.The author's vision draws inspiration from the experience of reconstructing a new transnational order in Europe after the ravages of the Second World War. The underlying theme focuses on the limitations of the purely national context as a framework for resolving the current political problems of the Israeli-Palestinian dilemma.